Pengaruh Pola Asuh Orang Tua dan Motivasi Belajar Terhadap Hasil Belajar Siswa dengan Metode Analisis Manova - Enon, Enon; Agus Mahardika, Eko (Journal of Comprehensive Science, 2024)
The pandemic period that lasted almost two years was enough to impact society. The resulting impacts include changes in work patterns, education, and activities in other communities. Face-to-face education has turned online, and jobs that were previously in the office have become online, impacting the life patterns of students and parents. Motivation in learning and parenting during this pandemic also has an impact on determining student learning outcomes. Seeing what is in today's society, researchers researched to determine the effect of parenting and learning motivation on student learning outcomes. The survey method used in this study and documentation of grades from the school, the overall sample used was 140 students of class VII, which was taken using purposive sampling. The analytical method used to analyze the data obtained in this study uses the MANOVA analysis method with the SPSS 25 application. Based on the data analysis carried out, it is obtained: (1) There is a significant influence between learning motivation and mathematics scores. (2) There is a significant influence between learning motivation on science scores. (3) There is a significant effect between parenting patterns on math scores. (4) There is a significant effect between parenting patterns on the IPA value.